Financial development, income inequality, and institutional quality: A multi-dimensional analysis - Cong Minh Huynh; Tran Nam Hoai (Cogent Economics & Finance, 2023)
Ambiguous impacts of financial development on income inequality in the literature imply that the impacts can be affected by other variables and may depend on different dimensions of financial development. This paper studies the effects of financial development with multi-dimensional analysis (financial depth, financial access, and financial efficiency) of two main categories (financial institutions and financial markets) and institutional quality on income inequality in 30 Asian countries in the period 2000-2019. Results show that the financial institutions development (FI), the financial institutions access (FIA), the financial institutions efficiency (FIE), and the financial markets access (FMA) reduce income inequality; but the overall financial development (OFD), the financial markets development (FM), the financial institutions depth (FID), and the financial markets depth (FMD) increase it. Notably, better institutional quality not only lessens income inequality but also moderates the effects of financial development on income inequality. Specifically, the improvement of institutional quality strengthens the beneficial effects of FI, FIA, FIE, and FMA on income inequality. Meanwhile, OFD, FM, FID, and FMD initially exacerbate income inequality until respective thresholds of institutional quality, and then beyond those levels of IQ, these indicators of financial development reduce income inequality. Results are robust with various estimators. These findings strongly support the importance of financial development with multi-dimensions and institutional reform in Asian countries as they have both direct and indirect impacts on income inequality through their mutual interactions.
Keywords: D31; D53; E02; O16; P48; 330; Asian countries; financial development; income inequality; institutional quality